9 IgG anti-malonedialdehyde-LDL antibodies are associated with low risk of cardiovascular events in a substudy of the anglo-scandinavian cardiac outcomes trial (Ascot), and are unrelated To LDL, CRP levels and statin treatment. Issue 20 (23rd September 2011) - Khamis, R Y; Johns, M; Thom, S; Mayet, J; McConnell, E; Stanton, A; Jeyapalan, S; Annon, S; Wrigley, S; Hughes, A; Haskard, D O
Abstract : Background: We aimed to determine whether measurement of antibodies to modified LDL predicts cardiovascular events. Methods: We studied ASCOT participants without diabetes with total cholesterol of ≤6.5 mmol/l and a total cholesterol/HDL ratio ≤4.5. IgG and IgM antibodies against malondialdehyde-modified LDL (MDA-LDL) and phosphorylcholine (PC) were measured by ELISA at baseline and after one year on atorvastatin (10 mg daily; n=100) or placebo (n=100). CRP, carotid intima-media thickness (CIMT), Framingham 10-year CVD Risk score (FRS) and total and LDL cholesterol (LDL) were determined. Results: Antibody levels did not correlate with baseline LDL, or LDL, CRP or CIMT at 1 year. Atorvastatin reduced LDL by 1.44 mmol/l (p<0.001, 95% CI 1.31 to 1.58 adjusted for age and sex), but did not influence IgG or IgM antibodies against MDA-LDL (p=0.74 and p=0.38) or PC (p=0.26 and p=−0.556). However, following adjustment for classical risk factors, baseline IgG anti-MDA-LDL levels predicted protection from cardiovascular events (HR=0.22, 95% CI 0.052 to 0.92; p=0.04). There was also a trend for IgG anti-MDA-LDL being protective after adjustment for FRS, (HR=0.33, 95% CI 0.089 to 1.20; p=0.09). Conclusion: IgG anti- MDA-LDL antibody levels are unrelated to LDL cholesterol levels, CRP, CIMT, and are not affected by treatment with atorvastatin. However, elevated levels are associated with significant protection against cardiovascular events and may be useful in clinical risk stratification for cardiovascular disease.